Analisis Manajemen Strategi dalam Meningkatkan Mutu Yayasan Pendidikan Islam - Ni’am, Muhammad Durrin; Firmansyah, Mohammad; Aminullah, Aminullah; Rofik, Moh; Febrianto, Febi; Alwahedi, Mohammad Abdul Aziz; Fikri, Rausyan; Mudarris, Badrul (CV. Lentera Literasi Indonesia, 2025)
Improving the quality of Islamic educational institutions is a strategic challenge in the modern era that demands the integration of Islamic values with a professional management system. This study analyzes the application of strategic management in improving the quality of education at the Nurul Masyithoh Lumajang Foundation, one of the oldest women's Islamic educational institutions in East Java. A qualitative approach with a case study design was used, with data obtained through in-depth interviews, observations, and documentation of foundation administrators, madrasah heads, teachers, and other related parties. The results of the study show that the foundation implements three main strategies: strengthening human resources through continuous training and coaching, developing a curriculum based on character and the values of Ahlussunnah wal Jama'ah, and implementing a structured and participatory quality management system. The implementation of this strategy has been proven to improve the academic quality, discipline, and religious character of students. This research emphasizes that strategic management based on Islamic values is an effective instrument in maintaining the sustainability of the quality of Islamic educational institutions. These findings can be a conceptual model for the development of similar institutions in facing the challenges of globalization and modernization of education.